PENGGUNAAN MEDIA TANAM YANG BERBEDA TERHADAP TIGA JENIS ANGGREK HASIL KULTUR IN VITRO PADA TAHAP AKLIMATISASI - Kiky Nurfitri Sari; Andika Prawanto; Indriati Meilina Sari (Jurnal Sains Agro, 2023)
Tissue culture is one of the in vitro propagation techniques for orchids that can be used to produce superior seeds. The final stage of the activity is the acclimatization process. The aim of acclimatization is to condition orchid seeds (in vitro) so that they can live in the real environment. One of the factors that influence the growth and development of seedlings at the acclimatization stage is the use of the type of planting media. Therefore, this study aims to obtain the right planting media used in the acclimatization stage of three types of orchids. This research was carried out in the plant house of the Horticultural Crop Study Program at the State Community Academy of Rejang Lebong in May - September 2022. The experimental design used was a factorial completely randomized design (CRD). The first factor is the type of planting medium (M1: fern, M2: husk charcoal, and M3: coffee husk), while for the second factor is the type of orchid plant which consists of A1: D. dicalor, A2: Phalaenopsis, and A3: Nodula. Each treatment was repeated three times in each experiment. carried out on the character of plant height, number of leaves, and stem diameter of orchid plants. The results showed that there was an interaction between the type of planting medium and the type of orchid on the character of the number of leaves. The best interaction performance was shown in the type of rice husk charcoal growing medium against the moon orchid.